PENGARUH LATAR BELAKANG PENDIDIKAN DAN PENGALAMAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI PT. INDOTIRTA SUAKA PULAU BULAN, BATAM - Simanjuntak, Samuel; Zamora, Ramon (University of Riau Kepulauan, 2016)
This study aims to examine and analyze the effect of Educational Background and Work Experience of the Employees Productivity at PT. Indotirta Suaka Moon Island, Batam. Data collect through questionnaires and conducted on 81 respondents. Analysis of the data in this study using SPSS version 20 statistical sample technique and is based on research estimates using Slovin formula with an error rate of 10% and testing techniques of data used in this study include testing the validity of the factor analysis, reliability test with Cronbach alpha. Classical assumption test and multiple linear regression analysis, to test and prove the research hypothesis. Hypothesis testing using t-test showed that varaiables and satisfaction Educational Background influence Employees Productivity and Work Experience variables affect the Employees Productivity. Then through the F test can be seen that two independent variables simultaneously affect the employees productivity. Figure adjusted R2 of 0.415 indicates that 41.5% variable employees productivity can be explained by the two independent variables in the regression equation, while the remaining 58.5% is explained by other variables outside the two variables used in the study.